2013
DOI: 10.2131/jts.38.495
|View full text |Cite
|
Sign up to set email alerts
|

Toxic effects of T-2 toxin and deoxynivalenol on the mitochondrial electron transport system of cardiomyocytes in rats

Abstract: -The in vitro effects of 2 representative mycotoxins, T-2 toxin and deoxynivalenol (DON), of trichothecene group on the electron transport system (ETS) of mitochondria in rat cardiomyocytes were investigated by measuring oxygen consumption rates (OCR). The ATP-linked OCR and the reserve capacity (RC) of the mitochondria ETS were quantified by a "mitochondria stress test" which was estimated by the OCR responses to oligomycin and carbonyl cyanide-p-trifluoromethoxyphenylhydrazone, with an extracellular flux ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…The present study showed that consuming DON-contaminated diets causes obvious oxidative stress to piglets from the change of analyzed indicators. Indeed, DON induced oxidative stress is widely observed in chickens [35], mice [36], pigs [13], rats [37], fish [38], and even cell lines isolated from human [39]. Intriguingly, our results demonstrated that supplementing glutamic acid to DON-contaminated piglet diet alleviates the oxidative stress caused by DON from the change of CAT, T-AOC, MDA and H 2 O 2 .…”
Section: Discussionsupporting
confidence: 50%
“…The present study showed that consuming DON-contaminated diets causes obvious oxidative stress to piglets from the change of analyzed indicators. Indeed, DON induced oxidative stress is widely observed in chickens [35], mice [36], pigs [13], rats [37], fish [38], and even cell lines isolated from human [39]. Intriguingly, our results demonstrated that supplementing glutamic acid to DON-contaminated piglet diet alleviates the oxidative stress caused by DON from the change of CAT, T-AOC, MDA and H 2 O 2 .…”
Section: Discussionsupporting
confidence: 50%
“…In several studies, trichothecenes affected also cellular and mitochondrial properties (Pace 1983), for example diminishing oxygen consumption of primary cardiomyocytes exposed to low-dose DON (Ngampongsa et al 2013) or in higher doses (100 μM DON), triggering cell apoptosis by the mitochondria-associated pathway (Bensassi et al 2012). In contrast to such acute, direct mitotoxic effects, it has been shown that an application of low-dose DON (200 ng/mL corresponding to 0.68 μM) to the basolateral compartment of membrane cultured IPEC-J2 cells triggered the messenger RNA (mRNA) expression of components of the citrate cycle and the oxidative phosphorylation (Diesing et al 2012), indicating the crucial role of mitochondria.…”
Section: Introductionmentioning
confidence: 99%
“…T-2 toxin is metabolized (hydrolyzed to HT-2) after ingestion, yielding multiple metabolites with known or less known toxicity and membrane association capability (9). Their mode of toxic action is rather divergent, as the inhibition of protein synthesis (specifically in eukaryotes) and inhibition of DNA synthesis (9), or the disruption of the mitochondrial electron transport system (26), augmented lipid peroxidation, affecting ultimately cell membrane integrity. According to Ngampongsa et al's study (26), the ATPlinked oxygen consumption rate of cardiomyocyte mitochondria is compromised by T-2 toxin, which is underpinned with our recent results, in which rabbit erythrocyte Na + /K + ATPase activity (the rate of ATP breakdown) was markedly lowered by T-2 toxin (33).…”
Section: Introductionmentioning
confidence: 99%
“…Their mode of toxic action is rather divergent, as the inhibition of protein synthesis (specifically in eukaryotes) and inhibition of DNA synthesis (9), or the disruption of the mitochondrial electron transport system (26), augmented lipid peroxidation, affecting ultimately cell membrane integrity. According to Ngampongsa et al's study (26), the ATPlinked oxygen consumption rate of cardiomyocyte mitochondria is compromised by T-2 toxin, which is underpinned with our recent results, in which rabbit erythrocyte Na + /K + ATPase activity (the rate of ATP breakdown) was markedly lowered by T-2 toxin (33). It was established that in the rat liver, T-2 toxin inhibits the mitochondrial electron transport system, concluding that mitochondria are possible hepatic targets of T-2 toxin action (27).…”
Section: Introductionmentioning
confidence: 99%